DNA BARCODING AND PHYLOGENETIC RELATIONSHIP OF RAY-FINNED FISH FAMILY SERRANIDAE (GENUS EPINEPHELUS) FROM THE COAST OF GWADAR BALUCHISTAN - Rabia Kausar; Asmatullah Kakar; Muhammad Shafi; Faiz Muhammad; Shagufta Sadozai; Amna sulaiman; Ayesha Allah Yar (Journal of Animal and Plant Sciences, 2025)
DNA barcoding is inevitable for identification and effectively replacing the traditional pattern of species taxonomy around the world. Species of the family Serranidae are commercially important and play a vital role in Pakistan economy. This family is in high demand in both domestic and international markets due to its white, tender, and flavorful meat, as well as its appealing texture, generating significant revenue. Many species exhibit close morphological characteristics, leading to confusion in accurate identification. The objectives of present study are to identify the grouper species based on morphological and molecular approaches. Epinephelus fish samples were collected with the assistance of local fisherman from the coast of Gawadar, Baluchistan. Besides the morphological identification approaches, the barcoding method became an integral tool for identification in by years and it replacing the traditional taxonomic approaches worldwide. In present study we became successful to identify the four species of Epinephelus, however the genetic distance revealed a diversity range of 0.00 to 0.19. Furthermore, the phylogenetic analysis detailed the close relationship between the species from China, Iraq, Iran, Malaysia, Bangladesh, India, Qatar, Saudi Arabia, Thailand, Canada and Tehran.
Keywords: DNA barcoding; Phylogenetic relationship; Epinephelus; N.J. (neighbor joining); Kimura distance; Gwadar